Réponses

2013-10-18T16:45:14+02:00
A=(8x-3)(8-7x)-(8x-3)(-x+1)=(-8-3)(-6x+7)=-(8x-3)(6x-7)
D=(5x-8)^2-(5x-7)(5x-8)=(5x-8)(5x-8-5x+7)=(5x-8)(-1)=-(5x-8)
E=16(x-1)^2+(3x-3)=16(x-1)^2+3(x-1)=(x-1)(16x-16+3)=(x-1)(16x-13)
F=(2x-7)^2-49=(2x-7)^2-7^2=(2x-7-7)(2x-7+7)=2x(2x-14)=4x(x-7)
G=(5x-4)^2-(3-2x)^2=(5x-4-3+éx)(5x-4+3-2x)=(7x-7)(3x-1)=7(x-1)(3x-1)
Pour B et C je pense qu'il y'a une erreur de frappe: j'ai fait les rectifications suivantes: 
B= 4(8x-6)(4x-3)^2 = 8(4x-3)^3
C=2(x+1)^2+3(x+1)=(x+1)(2x+2+3)=(x+1)(2x+5)